A couple‐based intervention for patients and caregivers facing end‐stage cancer: outcomes of a randomized controlled trial. Issue 1 (15th September 2011) - McLean, Linda M.; Walton, Tara; Rodin, Gary; Esplen, Mary Jane; Jones, Jennifer M.
Abstract Background We evaluated the effect of Emotionally Focused Therapy (EFT) [intervention (INT)], modified for the advanced cancer population versus standard care [control (CTL)], on marital functioning and psychosocial outcomes among distressed couples. EFT examines the ways couples process patterns of interaction, facilitating change. Methods Forty‐two patients with metastatic cancer and their caregivers were assigned randomly to receive eight sessions of EFT delivered by one EFT‐trained psychologist or standard care provided by multidisciplinary clinicians. Partners completed measures of marital functioning, depression, hopelessness, empathic caregiving (patient), and caregiver burden (caregiver) before randomization at baseline (T0), post‐intervention (T1), and 3‐month post‐intervention (T2). Data were analyzed using three‐way analyses of covariance; main effects were treatment, patient status, and sex. Multilevel modeling was also employed. Results At T1, INT group led to significant improvement in marital functioning (p ≤ 0.0001) and patients' experience of caregiver empathic care (p = 0.02) versus CTL group. Effect sizes for these differences were in the large range (d = 1.00). In both groups, patients showed a marginally higher mean score for marital functioning compared with caregivers [INT: M = 56.3, standard deviation (SD) = 4.6 vs M = 54.3, SD = 4.5; CTL group: M = 43.4, SD = 10.3 vs M = 42.4, SD = 6.8, respectively]. At T2, results were maintained. Conclusions The effectiveness of and adherence to the EFT couple intervention for patients facing advanced cancer were demonstrated in this study. Larger randomized control trials are needed to confirm these findings. Qualitative studies may help to further understand the mechanism by which such an intervention may act. Copyright © 2011 John Wiley & Sons, Ltd.